STUDY OF CLINICAL AND PATHOGENETIC EFFECTS OF ANTI-VIRAL DRUG BASED ON FAVIPIRAVIR IN COMORBID PATIENTS WITH COVID-19 AT THE OUTPATIENT STAGE OF TREATMENT - L. A. Balykova; O. A. Radaeva; K. Ya. Zaslavskaya; Yu. A. Kostina; M. S. Iskandyarova; E. V. Negodnova; V. V. Eremeev; L. F. Sabirov; E. V. Semeleva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
In many ways, arterial hypertension and obesity determine the likelihood of a severe course and lethal outcomes in COVID-19. This fact justifies the expediency of an early use of drugs with a direct antiviral action, the analysis of their efficacy not only in the acute, but also in the postcovid period.The aim of the research was to analyze the outpatient cards and case histories of the COVID-19 patients to study the effect of the early (up to the 5th day after the onset of the first symptoms of the disease) use of the drug based on favipiravir, on the frequency of patients' hospitalizations with arterial hypertension and obesity, as well as to determine the cytokine status characteristics of this patient category in the postcovid period.Materials and methods. "An open prospective comparative study of the "Areplivir®" (favipiravir) efficacy in the debut of COVID-19 in comorbid patients" was carried out in the Republic of Mordovia (the analysis of the hospitalizations frequency and blood levels of M-CSF, EPO in 218 patients, in terms of the use of the antiviral preparation).Results. According to the results of the analysis, it was found out that, despite the presence of comorbid conditions that increase the risk of developing a severe course of COVID-19, i.e. obesity and essential arterial hypertension, in the group of patients taking favipiravir, the need for hospitalization was twice as low (p < 0.05), in relation to the comparison group. The analysis of the cytokine status revealed that in the postcovid period, in the group that took the drug based on favipiravir at the outpatient stage, the average level of M-CSF was significantly lower (p> 0.05), and EPO was higher (p> 0.05) than in the patients from the group "without antiviral drugs at the outpatient stage". Indirectly, according to the previously obtained data, that acts as a potential marker for reducing the risk of long-term cardiovascular complications of COVID-19.Conclusion. This study showed that an early prescription of favipiravir contributes to a decrease in the rate of COVID-19 patients' hospitalization even against the background of concomitant hypertension and obesity, due to a decrease in the likelihood of moderate and severe courses of the disease, and also leads to an earlier objective and subjective recovery. The results demonstrated a high potential benefit of an early favipiravir use in the novel coronavirus infection and in the prevention of postcovid complications.